Pelatihan Perencanaan Bisnis untuk Meningkatkan Minat Wirausaha Siswa SMA 4 Palangka Raya - Kalalinggi, Septaria Yolan; Ompusunggu, Dicky Perwira; Rasidah (Journal of Appropriate Technology for Community Services, 2024)
Entrepreneurship is an indicator in seeing the progress of a nation and state. To become a developed country requires a minimum of 20% of entrepreneurs from the total workforce, while Indonesia is still below 8%. Therefore, the core of this community service program is to inspire the spirit of entrepreneurship from an early age to students. Hopefully, in the future, these students will become skilled and competent entrepreneurs. Technically, this entrepreneurship service is to provide a theoretical and practical understanding of entrepreneurship to teenagers, especially students of State Senior High School 4 Palangka Raya. This training is expected to be a provision for them after graduating from school, if they want to start their own business. The method involves training with various materials and visual materials related to entrepreneurship. At the beginning of the activity, students were given an understanding of entrepreneurship in theory, namely the history of entrepreneurship, business theory, financial statements, and business feasibility studies. After that, participants were given an understanding of entrepreneurship through speakers who came from practitioners / entrepreneurs. The material from the practitioner is the experience and tips of entrepreneurship. Then this activity was continued with questions and answers between participants and speakers. Evaluation was conducted through a pre-test (before material exposure) and post-test (after material exposure and Q&A) to measure students' understanding and interest in entrepreneurship. Before receiving the training, participants may feel afraid or hesitant regarding the risks that may arise during entrepreneurship. However, after receiving the training, students began to feel more confident and realized the positive impact they could experience if they were involved in entrepreneurship. This can also be seen from the increase in understanding by 36% of all participants.